The Extended Theory of Planned Behavior to Measure Sharia Investment Intention Among the Z Generation - Much. Maftuhul Fahmi; Eko Suprayitno; Indah Yuliana; Vivin Maharani Ekowati; Aunur Rofiq (Universitas Darussalam Gontor, 2024)
The growth of the Islamic economy in Indonesia, especially in the Islamic Capital Market and sukuk investments, has rapidly developed thanks to the active contribution of Generation Z. To develop a more comprehensive approach in Islamic investment behavior, it is crucial to understand the social and psychological factors. Therefore, this study focuses on examining the investment preferences of Generation Z in Islamic Capital Market, viewed from the perspective of Islamic financial literacy and religion. The Theory of Planned Behavior (TPB) is used to analyze attitudes, subjective norms, and Perceived Behavioral Control as mediators. This quantitative study uses an explanatory technique and a representative sample of 221 students from the Faculty of Economics at the Universitas Indonesia Maulana Malik Ibrahim Malang. The study utilizes purposive and proportional sampling methods. Google Forms were used to collect primary data and conduct surveys. A Likert scale (1–5) measured participant responses. SEM-PLS analysis was employed to assess 55 items across six variables in this study. The analysis was conducted using SmartPLS 3.0. The study reveals that Generation Z’s interest in the Islamic Capital Market is largely not driven by religion or financial knowledge in Islam. The Theory of Planned Behavior (TPB) variables can influence Generation Z’s intention to invest in Islamic Capital Market. The study indicates an indirect relationship between Islamic Financial Literacy and Religiosity with Generation Z’s intention to invest in Islamic Capital Market. Thus, the study concludes that Generation Z’s intention to invest in the Islamic Capital Market is more influenced by factors from the Theory of Planned Behavior (TPB) than by religion or Islamic financial literacy.